Financial literacy, financial behaviour and individuals' over-indebtedness - Santos, Elisabete (2013)
This work analyses the impact of financial literacy and financial behaviour of individuals on the likelihood of over-indebtedness, controlling for socioeconomic factors, the type of mortgage and the event of a negative income shock. Using the data from the 2009 National Financial Capability Study of the United States, we consider three self-reported measures of over-indebtedness: financial distress, arrears and foreclosure. Using the data from the National Financial Capability Study carried out in the United States in 2009, we have defined three measures of over-indebtedness – financial distress, arrears and foreclosure -, and constructed a financial literacy index and a financial behaviour index. The financial literacy index is constructed using questions on the compounding of interest rate, inflation, bonds and stocks, mortgage payment and risk diversification. The financial behaviour index is based on questions concerning individuals’ financial choices related with budget management, savings, bank accounts, credit, insurance and financial advice. Results show that gender matters for the intensity of over-indebtedness. Men have higher probability of experience financial distress or being in arrears but have lower probability of getting involved in a foreclosure process. In addition to the impact of socioeconomic factors, we conclude that financial literacy contributes to the prevention of over-indebtedness since individuals with higher levels of financial literacy are less likely of becoming over-indebted. Also, individuals who engage in positive financial behaviours, such as spending less than their own income, setting a ‘rainy day’ fund, using credit wisely or looking for financial advice, are less likely to experience severe financial difficulties. Independently of the level of financial literacy and of financial behaviour, experiencing a large drop in income is an important determinant of over-indebtedness.